THE EFFECT OF ALTITUDE ON THE GROWTH AND DEVELOPMENT OF TROJAN FIR (Abies nordmanniana subsp. equi-trojani [Asch. & Sint. ex Boiss] Coode & Cullen) SAPLINGS - Keleş, Seray Özden (FapUNIFESP (SciELO), 2020)
The altitude is an important factor to affect growth and development of saplings of tree.  This study, therefore, aimed to evaluate the influence of altitude on the morphological, anatomical and wood density properties of saplings of Abies nordmanniana subsp. equi-trojani [Asch. & Sint. ex Boiss] Coode & Cullen (Trojan fir). The present study was set up at two different altitude steps: 795 m (a.s.l. low-altitude) and 1350 m (a.s.l. high altitude). The morphological (stem height, diameter, degree of taper, pith proportion, bark proportion and xylem proportion) and anatomical (ray numbers, average ring width, ray height and width, tracheid length and width, tracheid lumen width and tracheid wall thickness) were determined at two altitudes. Wood density were also investigated. The morphological results showed that saplings grown at low-altitude had greater taper degree, pith radius, pith proportion and bark proportion than high-altitude. However, stem height, stem diameter, node number and xylem proportion were found to be higher in saplings grown at high-altitude than low-altitude. The growth of fir saplings increased with altitude. The results of anatomical measurements indicated different patterns in wood cell anatomy between two altitudes such that ring width, ray numbers, tracheid length and tracheid width were higher at low-altitude, whereas ray height, ray width, tracheid lumen width and tracheid wall thickness were greater at high-altitude. Wood density was also found to be higher in saplings grown at high-altitude. It could be suggested that growth and development of fir saplings were better when they were grown at high-altitude than low-altitude.
Keywords: Stem Morpholgy; Stem Morphology; Altitude; Sapling; Trojan Fir; Tree Growth; Trojan fir; Wood Anatomy; Tree Biomechanics; Tree Morphology; 15. Life on land